Evaluasi active design pada media perjalanan aktif di sekitar ruang publik kota - Raden Rangga Ilham Irfandian; Herman Wilianto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
The active design evaluation on the media of active living around urban public space The rise of development, technology and culture in urban communities has produced various positive and negative impacts, one of the negative impacts is the decline in public health factors and the increase of various cardiovascular diseases in urban communities caused by sedentary lifestyle. Based on this phenomenon we began to develop the Active Design principle. The active design is a design principles to makes some environment that can stimulate its users to carry out physical activity naturally. The active design principles has a significant impact on improving public health factors when applied around the centre of communities activities. Along with this phenomenon, the city of Bandung has carried out various revitalization on its public open spaces, one of which is revitalization in the Saparua park, which has become the centre of community activities in sports and recreation. This is a qualitative-descriptive study with the aim of evaluation. The research begins by formulating active design indicators from various literatures, then evaluating the object of study based on the indicators. Produce an understanding of the extent to which the principles of active design materialize on the object of study, the potential for future development and any manifestations that can be used as examples for design elsewhere. © 2019 Raden Rangga Ilham Irfandian, Herman Wilianto